The Padre Gomez Elementary School an institutional case study - Rivera, Josephine C. ([Quezon City s.n.], 1966)
This study provided an empirical description of an organization, a pilot elementary school, the Padre Gomez Elementary school, to determine how an elementary school fulfills its role in Philippine society.
Thesis (M.Ed.)--University of the Philippines
Keywords: Padre Gomez Elementary School, Manila